2021
DOI: 10.7759/cureus.16996
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Giant Upper Limb Malignant Melanoma

Abstract: Melanoma is rare among the Asian population. In Malaysia, there is little public awareness of melanoma compared to other types of cancer. Giant melanomas measuring more than 10 cm are rarely encountered and there are limited data available regarding this disease. We would like to report an unusual presentation of giant malignant melanoma of upper limb in a 62-year-old patient who presented with a five-month history of a progressively enlarging, painless mass on his left arm. This mass which measures 10 x 15 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Also unique to this case was the finding of a positive BRAF V600E mutation. BRAF mutations, while common in melanomas, were only found in two other cases of giant melanomas [ 4 , 5 ]. This genetic mutation, in a patient naive to systemic therapy, the patient’s functional status, and the metastatic nature of presentation, made treating with pembrolizumab an appropriate initial therapeutic option [ 14 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also unique to this case was the finding of a positive BRAF V600E mutation. BRAF mutations, while common in melanomas, were only found in two other cases of giant melanomas [ 4 , 5 ]. This genetic mutation, in a patient naive to systemic therapy, the patient’s functional status, and the metastatic nature of presentation, made treating with pembrolizumab an appropriate initial therapeutic option [ 14 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review study revealed that from 1960 to 2016, only 19 MM case reports had been published globally, and out of these, none were from Africa [ 10 ]. Of these, eight were on the trunk, six on the upper limb, four on the head, and only one on the lower limb (thigh) [ 1 , 10 , 11 ]. However, another evaluation of melanomas among Ethiopian patients 96 % predominance of nodular melanoma among 50 cases was described with only one case of Acral lentiginous melanoma from 1996 to 2005 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant melanoma is a neoplasm that develops from melanocytes [ 1 , 2 ]. In the earlier years, it was considered uncommon; however, reports show its incidence has increased, especially in the developed world [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations